The Influence of Perceived Risk and Trust in Adoption of FinTech Services in Indonesia - Meyliana, Meyliana; Fernando, Erick; surjandy, surjandy (CommIT (Communication and Information Technology) Journal, 2019)
The service level in community must be considered if it wants to continue to be used by the users. This research studies the adoption of Financial Technology (FinTech) services in the terms of trust and risk. The work employs the Technology Acceptance Model (TAM) theory as the theoretical basis combined with trust and perceived risk. The research method is quantitative. The data are analyzed by the Structural Equation Model (SEM) using Smart PLS V2.0. The researchers use a questionnaire in Google Form to collect the data. It is distributed online with the snowball data collection technique. As a result, 548 respondents are successfully gathered. The results indicate that the factor of users trusts influences perceived usefulness in the adoption to use FinTech services. However, the risk factor does not affect the use of FinTech services, which further does not influence the users’ attitude. The work contributes to the study of the adoption of FinTech services, which provides a view determining the users’ intention to use FinTech services in Indonesia.